Governance Mechanisms and Dividend Policy: Evidence From Industrial Companies in Indonesia - Monalisa Firdaus; Bram Hadianto (Owner : Riset dan Jurnal Akuntansi, 2025)
Profits attract the attention of stakeholders, especially creditors, managers, and shareholders. Creditors, either banks or bondholders, must be guaranteed that the company performs well because it must pay interest or coupons. For managers, the profits are one of the internal financing sources when the company retains them. If the company pays them for shareholders, dividends will exist, and vice versa. The related decision is also called dividend policy. For shareholders, dividends become the element of their wealth. This investigation aims to prove and analyze the impact of governance mechanisms on dividend policy with the population and samples from the industrial companies listed on the Indonesian capital market between 2017 and 2022. These mechanisms cover institutional ownership, supervisory board size, and liability policy. Besides, the samples are randomly taken from the population, and the data are analyzed using the Tobit regression model estimated by the maximum likelihood technique. After checking the associated hypotheses, this study concludes that institutional ownership and supervisory board size positively affect dividend policy. Unfortunately, a negative association occurs between liability and dividend policy. Based on these facts, public investors can consider choosing the company as the dividend payer based on the high institutional ownership, more supervisory board number, and low debt level.